RESPONS SISWA TERHADAP PRAKTIKUM PEMBUATAN DONAT JAHE PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Apriani, Apriani; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The laboratory experiment of making ginger (Zingiber officinale var. officinale) donut on sub chapter of Plant Role in Economy of Class X SMA / MA aimed to know students responses of laboratory work which was a new learning method on Sub Chapter of Plant Role in Economy Class X SMA / MA. This laboraatory experiment was a new breakthrough in the optimization of abundant local plants namely Ginger elephant (Zingiber officinale var officinale). This research used descriptive method and the subject was students class X MIPA 1 of MAN 1 Pontianak. Student responses was viewed used a response questionnaire given after the students carry out the experiment. The average percentage of students responses was 90% very high category, so that this laboratory experiment method was suggested implemented as a method of learning on Sub Chapter Role of Plant in Economy.Keywords: laboratory experiment, ginger, ginger donut, responses.